Implementation of a packet tower for diminution of furfural in the distillation process of cocuy pecayero - Leal Granadillo, Iván; Madrid Díaz, María; Rangel Molleda, Mirse; Martínez Bracho, Cornelio; Morán Guillén, Héctor (Revista Técnica de la Facultad de Ingeniería. Universidad del Zulia, 1970)
The distillation of cocuy liquor in the Pecaya”™s town, Sucre”™s Municipality of Falcon state, is an artisan process and the main problem for its sale is the high concentration of furfural and methanol into the beverage; hence, the aim of this investigation consisted in the designed, constructed and placed into operation to a packed tower than substituted the artisan rectifying column for to lessen the furfural”™s concentration into the beverage. The packed tower designed and constructed was a 0.45 m of diameter and 0.33 m of high of packed bed, this is equivalent to four theoretical plates of separation. For the evaluation was performed two distillations of 100% Agave cocui must; from the first distillation were obtained 44 fractions and 40 from the second distillation, which were analyzed by gas chromatography. According to the results, the incorporation of the packed tower into the distillation process of cocuy pecayero produced a diminution of the furfural”™s concentration lower than concentration detected. On the other hand, the concentration of methanol was slow respect to the artisan distillation; however, this concentration is higher to the limit of COVENIN 3662 norm.